2009
DOI: 10.1080/03630240903423980
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Single Mothers Making the Transition from Welfare to Work

Abstract: This study examined the quality of life of single mothers making the mandatory transition from welfare to work. The Australian government purported that the benefits of making this transition would include higher incomes, better social participation, and improved wellbeing. It is currently unknown, however, how single mothers currently engaged in welfare to work programs evaluate their quality of life. Quality of life scores for 334 single mothers engaged in welfare to work in Australia were compared with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Perceived social support, rather than the actual support received, plays an important role in predicting psychological well‐being and HRQOL (Cook et al. , Weinberg ). In contrast, impaired social support is one of the most powerful risk factors for PTSD vulnerability (Brewin et al , Ozer et al ), as well as depression (Cruwys et al , Lindfors et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived social support, rather than the actual support received, plays an important role in predicting psychological well‐being and HRQOL (Cook et al. , Weinberg ). In contrast, impaired social support is one of the most powerful risk factors for PTSD vulnerability (Brewin et al , Ozer et al ), as well as depression (Cruwys et al , Lindfors et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in maternal self-esteem (Al-Yagon, 2010), self-efficacy (Holland et al, 2011;Jackson, 2000), intellectual capacity (Bradley, Corwyn, Pipes McAdoo, & García Coll, 2001;McLoyd, 1998), mental health status (Ensminger, Hanson, Riley, & Juon, 2003;Osborne et al, 2012), past experiences of abuse (Wright, 2010), parenting styles (Ekas, Lickenbrock, & Whitman, 2010;Jackson, Brooks-Gunn, Huang, & Glassman, 2000), and gender stereotypes (Kimmel, 2000;Lamke & Filsinger, 1983;Wright, 2007), among others, have been cited as correlates of child outcomes and have then been interpreted as proxies for maternal well-being. Studies utilizing maternal-level indicators to assess maternal well-being have typically employed measures of functioning as well, including income-to-needs ratios (McLanahan & Garfinkel, 1995), mental health status (Mistry, Stevens, Sareen, De Vogli, & Halfon, 2007;Rafferty, Griffin, & Robokos, 2010), employment status (Chatterji, Markowitz, & Brooks-Gunn, 2013;Lennon, Blome, & English, 2001), marital status (Cooper, McLanahan, Meadows, & Brooks-Gunn, 2009), or other objective indicators (Cook, Davis, Smyth, & McKenzie, 2009;Desjardins, Zelenski, & Coplan, 2008;Kossek, Pichler, Meece, & Barratt, 2008). Although these quantitative indicators of maternal functioning have been associated with positive outcomes for children, including improved academic achievement (e.g., Wright, 2010), positive social-emotional development (e.g., Jackson et al, 2000), and increased self-esteem (e.g., McCloyd, 1998;Moore, Murphey, & Bandy, 2012), researchers have rarely explored which indicators low-income women utilize to self-assess their own functioning and quality of life.…”
Section: Maternal Functioning As a Proxy For Well-beingmentioning
confidence: 99%
“…Despite these potential benefits, sole mothers in paid employment still have poorer health outcomes than do partnered mothers in paid employment (Afifi, Cox, & Enns, ; Dziak, Janzen, & Muhaarine, ). For example, employed sole mothers in Europe, Australia, and Canada have reported lower levels of life satisfaction, happiness, mental health, and positive affect than employed partnered mothers (Bull & Mittelmark, , ; Cook et al, ; Dziak, Janzen, & Muhaarine, ). Further, employed sole mothers are more likely than employed partnered mothers to experience financial hardship, a perceived lack of social support, and poorer psychosocial work quality (Cook et al, ; Dziak et al, ).…”
Section: Overview: Sole and Partnered Mothers In Paid Employmentmentioning
confidence: 99%
“…For example, employed sole mothers in Europe, Australia, and Canada have reported lower levels of life satisfaction, happiness, mental health, and positive affect than employed partnered mothers (Bull & Mittelmark, , ; Cook et al, ; Dziak, Janzen, & Muhaarine, ). Further, employed sole mothers are more likely than employed partnered mothers to experience financial hardship, a perceived lack of social support, and poorer psychosocial work quality (Cook et al, ; Dziak et al, ). Buehler et al () reported that sole mothers in the United States also are more vulnerable to role strain than are partnered mothers.…”
Section: Overview: Sole and Partnered Mothers In Paid Employmentmentioning
confidence: 99%